Cost Analysis of Combination Diuretic Therapy with Ace-Inhibitors to Diuretic Therapy without Ace-Inhibitors in Heart Failure Patients (Bangladesh Journal of Medical Science, 2016)
Background: Heart failure is the final stage of the entire heart disease and become a major health problem because of the high morbidity and mortality. Diuretic combination therapy with ACE inhibitors compared to diuretic therapy without ACE inhibitors will affect the costs and hospitalization for heart failure patients; so it can be used to study Pharmacoeconomics.Method and Design: This study is an analytic observational retrospective cohort study design. Researchers compared the cost analysis between groups having diuretic combination therapy with an ACE inhibitor and diuretic therapy without ACE inhibitors. Data taken with a total sampling of heart failure databases claimed prescribing health insurance PT. ASKES Persero between January 1, 2010 until December 31, 2011.Results: Out of the 377 patients of the study population, 64 patients received combination therapy with ACE inhibitors and diuretics, and 60 patients received diuretic therapy without ACE inhibitors. The analysis showed that the total cost was Rp. 4.96 million and Rp. 5.14 million; the average total inpatient days a year was 10.67 days and 7.00 days.Conclusion: This study showed that the diuretic combination therapy with an ACE inhibitor is more cost-effective. Further research is needed to assess the total costs and effectiveness of therapy with more number of subjects and longer periods.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.368-375